Management and outcomes of traumatic paediatric spinal cord injuries in low- and middle-income countries: a scoping review protocol. Issue 2 (13th April 2022) - Dalle, David Ulrich; Ooi, Setthasorn Zhi Yang; Sriram, Smrithi; Bandyopadhyay, Soham; Egiz, Abdullah; Kotecha, Jay; Kanmounye, Ulrick Sidney; Higginbotham, George; Bankole, Nourou Dine Adeniran
Abstract: Background: Traumatic spinal cord injury (TSCI) accounts for a significant proportion of deaths and disability worldwide and this is largely concentrated in low- and middle-income countries (LMICs). Though rare, a subset of TSCIs occurs in children, which can lead to long-term comorbidities if not managed within the optimal time frame. However, the lack of pre-hospital care, infrastructure and specialist manpower in LMICs may pose a challenge for health practitioners to provide quality and consistent standard of care to the children. The variety in practice and lack of clarity on management and outcomes of TSCIs in LMICs necessitates an evaluation of the literature. This scoping review protocol outlines how the authors will address the said topic of interest. Methods: MEDLINE, Embase and Global Index Medicus will be searched from database inception to date in order to identify the relevant studies. Paediatric patients (ages 18 or below) with a TSCI managed in an LMIC country will be included. Surgical and conservative management of TSCIs will be considered. Original research, reviews, commentaries, editorials and case reports will be included. Results: Primary outcomes will include TSCI epidemiology, presentation, management, morbidity, mortality and long-term complications. Secondary outcomes will include delays in receiving care. Discussion: This scoping review will be the first to evaluate the current landscape of paediatric TSCI management and outcomes in LMICs, highlighting pertinent themes that may be used to guide further research as well as health system strengthening efforts by policymakers and stakeholders.